A surveillance system for monitoring, public reporting, and improving minority access to cancer clinical trials - Carpenter, William R. (2012)
BACKGROUND: The Institute of Medicine (IOM) has recommended that each person with cancer should have access to clinical trials, which have been associated with improving care quality and disparities. With no effective enrollment monitoring system, patterns of trial enrollment remain unclear. PURPOSE: We developed a population-based, statewide system designed to facilitate monitoring of cancer trial enrollment and targeting of future interventions to improve it. METHODS: Person-level cancer incidence data from the North Carolina Central Cancer Registry (NCCCR), person-level treatment trial accrual data from the National Cancer Institute (NCI), and county-level Area Resource Files (ARF) measures for 12 years, 1996–2007, were studied. De-identified person-level data necessitated county-level analysis. Enrollment rates were estimated as the ratio of trial enrollment to cancer incidence for each race, gender, year, and county combination. Multivariable analysis examined factors associated with trial accrual. Sensitivity analyses examined spurious fluctuations and temporal discordance of incidence and enrollment. RESULTS: The NCI treatment trial enrollment rate was 2.39% for whites and 2.20% for minorities from 1996 to 2007, and 2.88% and 2.47%, respectively, for 2005–2007. Numerous counties had no minority enrollment. The 2005–2007 enrollment rates for white and minority females was 4.04% and 3.59%, respectively, and for white and minority males was 1.74% and 1.36%, respectively. Counties with a medical school or NCI Community Clinical Oncology Program (CCOP)-affiliated practice had higher trial enrollment. LIMITATIONS: We examined NCI trial accrual only – industry-sponsored and investigator-initiated trials were excluded; however, NCI studies comprise the majority of all clinical trial participants. Delays in data availability may hinder immediacy of population-based analyses. CONCLUSIONS: Model stability and consistency suggest this system is effective for population-based enrollment surveillance. For North Carolina, it suggests a worsening disparity in minority trial enrollment, though our analyses elucidate targets for intervention. Regional enrollment variation suggests the importance of access to clinical research networks and infrastructure. Substantial gender differences merit further examination.